Effect of CT manifestations of cholesteatoma on MMP-2, MMP-9 and IL-6 in the serum of patients - Wu, Yingzhe (Exp Ther Med, 2019)
Effect of CT manifestations of cholesteatomatous otitis media on matrix metalloproteinase-2 (MMP-2), matrix metalloproteinase-9 (MMP-9) and interleukin-6 (IL-6) in the serum of patients was investigated. A total of 176 patients with cholesteatomatous otitis media were enrolled as the study group and 181 patients with simple otitis media were enrolled as the control group. Patients were admitted to the Changxing People's Hospital from January 2010 to December 2016. The patients in the study group were classified according to the 64-row spiral CT diagnosis. The expression levels of MMP-2, MMP-9 and IL-6 in the serum of the selected patients were detected by ELISA. MMP-2, MMP-9 and IL-6 expression levels in the study group were higher than those in the control group (P<0.05). MMP-2, MMP-9 and IL-6 expression levels in the serum of the patients with injured ossicular chain were significantly higher than those in the serum of patients with injured malleus or incus (P<0.05), and significantly higher than those in the serum of patients with intact ossicular chain (P<0.05). The levels of MMP-2, MMP-9 and IL-6 in the serum of the patients whose malleus or incus was injured were higher than those in the serum of the patients with intact ossicular chain (P<0.05). There was an obvious positive correlation between the injury degree of different sclerotins in CT manifestations of the patients in the study group and MMP-2, MMP-9, and IL-6 (P<0.05). The high expression levels of MMP-2, MMP-9 and IL-6 in the serum of patients with cholesteatomatous otitis media were positively correlated with the injury degree of ossicle, which may be a sign of poor prognosis of cholesteatomatous otitis media.